Dynamic compressive material properties of clay bricks at different strain rates. (20th December 2018) - Zhang, Xihong; Chiu, Yu-Wen; Hao, Hong; Hsieh, Ariel; Salter, Nigel; Cui, Jian
Highlights: Quasi-static and dynamic compressive tests were performed on clay bricks. Stress-strain curves were derived at strain rates from quasi-static state to about 337 s −1 . Dynamic amplification effect to brick properties were discussed. Empirical formulae of DIFs were derived from the test results. Abstract: It is commonly known that materials behave differently under static and dynamic loadings. Clay brick is a vastly used building material. Systematic studies on the dynamic material behaviours of clay bricks are still very limited in the open literature, and the dynamic effect on clay brick material properties is not well investigated. This study carried out both low-speed and high-speed compressive tests on three types of clay bricks, i.e. high-strength, mid-strength and low-strength, made with Western Australia clays. The compressive strengths, ultimate strains and Young's modulus of the three different types of bricks at different strain rates (from 1.67 × 10 −6 /s to 0.08/s and 190/s to 337/s) were quantified. The test results showed the compressive strength was very sensitive to strain rate effect, while the ultimate strain and Young's modulus also exhibited strong strain rate dependency in high strain rate range but appears to be less sensitive to strain rate in the low strain rate regime. Based on the test results, empirical relations of dynamic increase factor (DIFs) for compressive strength, ultimate strain and Young's modulus with respect to strain rate were derived for each type of brick. Discussions and comparisons were made on the dynamic fracture processes and specimen fragments to explain the dynamic enhancement in brick mechanical properties.